An easy method of preparing ozone gas sensors based on ZnO nanorods1. Issue 25 (21st March 2015) - Catto, Ariadne C.; da Silva, Luís F.; Ribeiro, Caue; Bernardini, Sandrine; Aguir, Khalifa; Longo, Elson; Mastelaro, Valmor. R.
<x xml:space="preserve">Abstract</x> One-dimensional (1D) ZnO nanorod-like structures were successfully grown via a hydrothermal method to be used as an ozone gas sensor.